Recalcitrant Dermatomyositis Treated With Anifrolumab - Shivang Chaudhary; Meghan Baumer; Laura Upton; Samantha Ong; Kristin Smith; Daniel West; Adam Kilian (ACR Open Rheumatology)
Dermatomyositis is an idiopathic inflammatory myopathy which can present with distinctive skin features. Despite the many treatment modalities for the treatment of dermatomyositis some patients remain refractory to treatment. We present a case of a 38‐year‐old man with recalcitrant dermatomyositis who was successfully treated with the interferon α receptor 1‐inhibiting monoclonal antibody anifrolumab. Many studies have shown a correlation between dermatomyositis disease activity and the type 1 interferon pathway activity. We believe anifrolumab may be a promising option for severe cutaneous dermatomyositis.